Kearifan Tradisional Suku Maybrat Dalam Perburuan Satwa Sebagai Penunjang Pelestarian Satwa - Pattiselanno, Freddy; Mentansan, George (UI Scholars Hub, 2010)
Widlife management as food resources in the tropical areas is very rarely done. Traditional wisdom as an aspect that plays an important role in wildlife sustainability still put into practice by certain tribals. Study on traditional wisdom of Maybrat ethnic group was done to observe the practice of traditional wisdom create important impact to the effort of wildlife sustainability in Sorong Selatan Regency. The results indicate that traditional wisdom practice such as the use of hunting tools, places for hunting and wildlife hunted that indirectly give positive impact in order to support wildlife sustainability in Sorong Selatan.